Sports Athletes' Attitude, Motivation, Responsibility, and Personality Psychological Survey - Rubiyatno, Rubiyatno; perdana, rahmat putra (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objective. The objective of this study is to analyze the psychology of sports athletes through the lenses of attitude, motivation, responsibility, and personality. Materials and methods. The instrument utilized in this study comprised a questionnaire form, in which each athlete completed four distinct types of assessments: Attitude, Motivation, Responsibility, and Personality tests. This study included 20 students from the Sports Coaching Education Study Program, all of whom have demonstrated proficiency in football. These students attended lectures from semester 2 to semester 6 and have participated in various regional championships, showcasing a solid understanding of the game. Results. The findings of this study, derived from data collected via a questionnaire, are categorized as Very Less, Less, Sufficient, Good, and Very Good. The assessment involved 20 athletes and focused on four key categories: Attitude, Motivation, Personality, and Responsibility. In the Attitude category, 14 athletes achieved Good scores (70%), while 6 additional athletes attained Very Good results (30%). The mean score of the test outcomes for PKO soccer sports students in the Attitude category was rated as Good. The findings in the Motivation category indicate that most PKO soccer sports students demonstrated strong motivation, with 65% (13 athletes) receiving Good scores and 35% (7 athletes) achieving Very Good scores. Furthermore, in the Personality category, 8 athletes achieved Good scores, representing 40%, while 12 athletes, or 60%, attained Very Good scores. Conclusion. Demonstrates the students' excellent character. Conversely, in the Responsibility category, every athlete achieved a Good score, reflecting a perfect 100% performance.